The Sermon as Essay: James Baldwin as Contemplative Preacher (Homiletic, 2024)
From the ages of fourteen to seventeen, James Baldwin was an African American Pentecostal preacher, and this church period of his life significantly impacted the entire corpus of his writing. One of Baldwin’s most celebrated essays, “Down at the Cross,” was labeled by one scholar as “the essay that comes closest to representing his ideas in total, not in a schematic way, but in the form of a mature and exemplary worldview.” It is, in fact, a sermon. I propose that “Down at the Cross” is an African American sermon essay in the contemplative tradition and worthy of serious study in order to expand and encompass the often unheralded tradition of the African American contemplative sermon that invites hearers into their own conversation with God.